Global Luxury Organizational Change and Emerging Markets since the 1970s (Springer Singapore, 2018)
This book explores the luxury industry and how it has undoubtedly been one of the fastest-growing sectors since the 1970s, and one in which Europe has managed to strengthen its competitiveness in the world market. While many aspects of globalization remain abstract and intangible, the luxury industry has created markets where previously there were none, by educating Japanese about the history of French handbags, Chinese about the finest wines, and setting global standards for an elite, inspirational lifestyle. In this edited volume, a wide range of scholars comes together to analyze the history of the business and the innovations in management and marketing that have emerged from it. Invaluable for scholars, industry figures, and dilettantes alike, it will define the field of study for years to come. .